Acitretin-induced alopecia areata: a case report. (September 2015) - Ozlu, Emin; Karadag, Ayse Serap; Akdeniz, Necmettin; Uzuncakmak, Tugba Kevser
Abstract Alopecia areata is a common form of non-scarring hair disorder. The development of alopecia areata during anti-psoriatic treatment has been reported with the systemic therapies such as infliximab, etanercept, adalimumab, alefacept and efalizumab. Retinoid-induced alopecia areata on the eyelash and eyebrow has not been reported in the literature. We report a female patient who presented with alopecia areata of the eyebrow and eyelash one month after the initiation of acitretin therapy for psoriasis.